Aluminum powder material for N-type silver aluminum paste and its application

By using aluminum powder materials with suitable median diameter and optimized preparation technology, a dense oxide layer is formed, combining glass powder and silver powder, silver pinning pits and blockages caused by diffusion of aluminum powder and silicon substrate in N-type solar cells are solved. The network problem improves the conversion efficiency and printing efficiency of the battery.

CN116759134BActive Publication Date: 2025-01-07NANTONG AISHENG NEW ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310573169.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-19
Publication Date
2025-01-07
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

The diffusion of aluminum powder and silicon substrates in existing N-type solar cells leads to silver aluminum pinning pits, which increases the limitation of the battery's opening pressure reduction and conversion efficiency. The large particle size of aluminum powder can easily cause grid blockage, affecting printing performance. .

Method used

Aluminum powder material with a median diameter D50 of 1-3μm and a maximum particle D100 <4.5μm is used, and atomization is performed in a mixed atmosphere of nitrogen and oxygen to form a dense oxide layer, combining glass powder and silver powder, and silver powder is optimized. The preparation process controls the ratio and particle size of aluminum powder to silver powder and reduces the contact resistivity.

Benefits of technology

It effectively reduces electron-hole recombination, reduces metallization recombination, improves the open circuit voltage and photoelectric conversion efficiency of the battery cell, solves the problems of printing network blocking and pinning pits, and extends the life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004239279260000011
    Figure HDA0004239279260000011
  • Figure HDA0004239279260000012
    Figure HDA0004239279260000012
  • Figure HDA0004239279260000021
    Figure HDA0004239279260000021
Patent Text Reader

Abstract

The present invention discloses an aluminum powder material for N-type silver aluminum paste, wherein the median diameter D50 of the aluminum powder material is 1-3 μm, and the maximum particle D100 is less than 4.5 μm. The present invention can reduce the silver aluminum pinning pits formed while not affecting the formation of good ohmic contact of the silver aluminum paste on the front of the N-type battery during the metallization process, thereby reducing metallization recombination, increasing the open circuit voltage of the battery, and improving the photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aluminum powder material for N-type silver aluminum paste and application thereof, and relates to H01B, and in particular to the field of conductive materials containing metals or alloys. Background Art

[0002] With the development of society, the energy crisis is becoming more and more serious. It is an inevitable trend for the development of modern society to find new energy sources to replace traditional fossil fuels. Solar energy resources are an inexhaustible clean energy. It has become a reality to convert solar energy into electrical energy. Solar cells are becoming an important source of electricity supply. Compared with traditional P-type cells, N-type solar cells have the advantages of high conversion efficiency, high bifaciality, low temperature coefficient, no light decay, and good weak light effect. However, the pursuit of further improvement of the conversion efficiency of N-type cells and reduction of production costs are also the goals that the photovoltaic field has been pursuing. The factors affecting the conversion efficiency of solar cells mainly include grid line shielding, grid line contact resistance, carriers, etc. The existing printing paste has the phenomenon of large particles blocking the network. Aluminum powder can promote the formation of good ohmic contact on the front silver aluminum paste of N-type cells during the metallization process, but aluminum powder and silicon substrate diffuse with each other to form silver aluminum pinning pits, which are easy to break through the PN isolation junction, resulting in a decrease in the opening voltage, which seriously affects the battery efficiency. Therefore, it is very important to develop an aluminum powder material that can reduce the recombination of electron-hole pairs, is not easy to form silver aluminum pinning pits, reduces metallization recombination, and increases the opening voltage.

[0003] Chinese invention patent CN201410369114.3 discloses an aluminum powder for aluminum paste of crystalline silicon solar cells, a preparation method and a solar cell containing the aluminum powder, by adding D 50 ≤1 micron silica and D 50 Boron powder ≤1 micron, the addition of the two prevents silicon dioxide from reaching a molten state when the aluminum paste is sintered, avoiding excessive shrinkage of the edges of the aluminum sheet and reducing warping. However, when applied to N-type batteries, there is a problem of breaking through the PN isolation junction, which reduces the conversion efficiency. Chinese invention patent CN202011242618.0 discloses a silver-aluminum paste for the front side of an N-type high-efficiency battery. The mass ratio of aluminum powder to silver powder is 1: (78-85), which can improve the conductivity of the overall silver-aluminum paste and reduce the contact resistance of the final prepared battery. However, the particle size of the aluminum powder is slightly larger, which can easily cause problems such as blocking the screen or scratching the screen, affecting the printing of solar cells. Summary of the invention

[0004] In order to improve the comprehensive performance of silver-aluminum paste used in N-type batteries and optimize the performance of aluminum powder in the silver-aluminum paste, the first aspect of the present invention provides an aluminum powder material for N-type silver-aluminum paste, wherein the median diameter D50 of the aluminum powder material is 1-3μm and the maximum particle D100 is less than 4.5μm.

[0005] As a preferred embodiment, the shape of the aluminum powder material is selected from spherical, flake and star-shaped.

[0006] As a preferred implementation manner, the oxygen mass fraction of the aluminum powder material is less than 2%, and the initial oxidation temperature of the aluminum powder material is greater than 625°C.

[0007] As a preferred embodiment, the method for preparing the aluminum powder material comprises the following steps:

[0008] (1) Under the protection of nitrogen gas, the aluminum ingot is heated to 700-1000° C. in a smelting furnace to melt into aluminum liquid and keep the temperature, and then the obtained aluminum liquid is transported to an atomization chamber with a mixed gas as an ambient gas through an aluminum liquid guide pipe. At the same time, the mixed gas is sprayed through a tightly coupled gas atomization nozzle to atomize the aluminum liquid to form atomized aluminum liquid droplets. Then, under the cooling and protection of the ambient gas, the aluminum liquid is cooled and rapidly solidified to form atomized aluminum powder, and the cooling temperature is 200-400° C.;

[0009] (2) Using a nitrogen-protected airflow pulverizer to classify aluminum powder, under the protection of nitrogen gas, the aluminum powder prepared in step 1 is classified into aluminum powder materials with a particle size of less than 4.5 μm by adjusting the equipment air pressure to 0.5-0.7 MPa and the classification wheel speed to 270-320 Hz.

[0010] As a preferred implementation, the mixed gas is a mixed gas of nitrogen and oxygen, and the volume fraction of oxygen is 1-4%.

[0011] In an N-type semiconductor solar cell, electrons are majority carriers and holes are minority carriers. The number of electrons that transition from the donor energy level to the conduction band through thermal excitation increases greatly. The number of electrons in the semiconductor conduction band is far greater than the number of holes in the valence band, and the conductivity increases. However, the recombination of electrons and holes before they are effectively utilized will reduce the photoelectric conversion efficiency. The applicant found that removing large particles from aluminum powder and controlling the aluminum powder D100 to less than 4.5 microns can not only solve the problem of screen blocking in slurry printing, but also improve the pinning pits formed by the mutual dissolution of aluminum and silicon, reduce metallization recombination, and increase the opening voltage of the cell.

[0012] The applicant further found that the aluminum powder prepared by using a mixed gas protective atmosphere with an oxygen content of 2% has a low oxygen content and a dense oxide layer of the aluminum powder. The possible reason is speculated to be: using a mixed atmosphere of oxygen and nitrogen, the mixed gas with an oxygen content of 2% is wrapped by the mixed gas in the atomization chamber at the moment when the aluminum slurry forms aluminum liquid droplets. Since the proportion of oxygen in the nitrogen-oxygen mixed atmosphere is extremely low, the nitrogen pressure in the mixed gas is high, and oxygen reacts with the surface of the aluminum droplets in an instantaneous oxidation reaction. The aluminum oxide layer formed is not easy to form loose holes, thereby forming a dense aluminum oxide layer. The applicant further found that the starting oxidation temperature>625°C can further reduce the contact resistivity, reduce metallization recombination, and improve the photoelectric conversion efficiency.

[0013] The second aspect of the present invention provides an application of an aluminum powder material for N-type silver-aluminum paste, which is applied to the preparation of N-type silver-aluminum paste. The raw materials for preparing the N-type silver-aluminum paste include, by weight: 0.5-3 parts of aluminum powder material, 3-10 parts of glass powder, 70-90 parts of silver powder, and 5-15 parts of organic carrier.

[0014] As a preferred embodiment, the glass powder is a PbO-B2O3-ZnO-SiO2 glass powder, with a softening temperature of 300-500°C and a particle size D50 of 0.6-2 μm.

[0015] As a preferred embodiment, the particle size D50 of the silver powder is 1-3 μm.

[0016] As a preferred embodiment, the organic vehicle comprises, by weight, 0.8-3 parts of a binder resin, 2-6 parts of a solvent and 0.7-3.8 parts of an auxiliary agent.

[0017] The binder resin is selected from one or a combination of acrylic resin, ethyl cellulose, cellulose acetate butyrate, PVB (polyvinyl butyral ester), hydrogenated rosin ester resin, and thermoplastic elastomer.

[0018] As a preferred embodiment, the solvent is selected from one or a combination of diethylene glycol dibutyl ether, diethylene glycol butyl ether acetate, diethylene glycol butyl ether, dimethyl adipate, alcohol ester dodecahydrate, tripropylene glycol monomethyl ether, and alcohol ester hexadecene.

[0019] As a preferred embodiment, the auxiliary agent includes, by weight, 0.1-0.8 parts of dispersant, 0.1-1 parts of silicone oil and 0.5-2 parts of thixotropic agent.

[0020] As a preferred embodiment, the silicone oil includes but is not limited to methyl silicone oil, vinyl silicone oil, amino silicone oil, or a combination of several thereof.

[0021] As a preferred embodiment, the thixotropic agent is selected from one or a combination of polyethylene wax, polyamide wax, and hydrogenated castor oil.

[0022] As a preferred embodiment, the method for preparing the N-type silver-aluminum paste comprises the following steps:

[0023] (1) Mix aluminum powder material and glass powder evenly, add organic carrier, stir evenly, then add silver powder, stir evenly;

[0024] (2) Grind with a three-roll mill for 5-8 hours and filter with a 500-mesh filter to obtain N-type silver-aluminum slurry.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The aluminum powder material used for N-type silver aluminum paste of the present invention has a median diameter D50 of 1-3 μm and a maximum particle D100 of less than 4.5 μm, which can not only solve the problem of screen blocking during paste printing, but also improve the pinning pits formed by the mutual dissolution of aluminum and silicon, reduce metallization recombination, and increase the opening voltage of the battery cell.

[0027] (2) The aluminum powder material for N-type silver-aluminum paste described in the present invention adopts a mixed gas protective atmosphere with an oxygen content of ~ during the preparation process. The prepared aluminum powder has a low oxygen content and a dense oxide layer. It is used in the silver-aluminum paste of N-type batteries. The contact resistivity is low and the service life is long.

[0028] (3) The aluminum powder material for N-type silver-aluminum paste of the present invention has a weight ratio of aluminum powder material to silver powder of (0.5-3): (70-90). While ensuring a low contact resistance, it will not lead to an increase in electron-hole recombination, a decrease in the open-circuit voltage of the battery, and poor printing performance.

[0029] (4) The aluminum powder material for N-type silver-aluminum paste described in the present invention can reduce the silver-aluminum pinning pits formed without affecting the formation of good ohmic contact of the silver-aluminum paste on the front side of the N-type battery during the metallization process, thereby reducing metallization recombination, increasing the open circuit voltage of the battery, and improving the photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The differential scanning calorimetry (DSC) spectrum of the aluminum powder material prepared in Example 1;

[0031] Figure 2 This is an electron microscope image of the aluminum powder material prepared in Example 1;

[0032] Figure 3 The surface electron microscope image of the cell obtained by applying the aluminum powder material prepared in Comparative Example 1 to N-type silver aluminum paste;

[0033] Figure 4 This is an electron microscope image of the cell surface obtained by applying the aluminum powder material prepared in Example 1 to N-type silver-aluminum paste. DETAILED DESCRIPTION

[0034] Raw materials not explicitly described in this application are all commercially available.

[0035] Example 1

[0036] An aluminum powder material for N-type silver aluminum paste, wherein the median diameter D50 of the aluminum powder material is 1-3 μm, and the maximum particle D100 is less than 4.5 μm.

[0037] The aluminum powder material is spherical in shape; the oxygen content of the aluminum powder material is less than 2% by mass, and the initial oxidation temperature of the aluminum powder material is 630°C. The differential scanning calorimetry DSC spectrum is shown in Figure 1 .

[0038] The preparation method of the aluminum powder material comprises the following steps:

[0039] (1) Under the protection of nitrogen gas, the aluminum ingot is heated to 900° C. in a smelting furnace to melt into aluminum liquid and keep the temperature, and then the obtained aluminum liquid is transported to an atomization chamber with a mixed gas as an ambient gas through an aluminum liquid guide pipe. At the same time, the mixed gas is sprayed through a tightly coupled gas atomization nozzle to atomize the aluminum liquid to form atomized aluminum liquid droplets, and then, under the cooling and protection of the ambient gas, it is cooled and rapidly solidified to form atomized aluminum powder, and the cooling temperature is 300° C.;

[0040] (2) Using a nitrogen-protected airflow pulverizer to classify aluminum powder, under the protection of nitrogen gas, the aluminum powder prepared in step 1 is classified into aluminum powder materials with a particle size of less than 4.5 μm by adjusting the equipment air pressure to 0.6 MPa and the classification wheel speed to 300 Hz.

[0041] The mixed gas is a mixed gas of nitrogen and oxygen, and the volume fraction of oxygen is 2%.

[0042] The electron microscope image of the prepared aluminum powder material is shown in Figure 2 .

[0043] An application of aluminum powder material for N-type silver-aluminum paste is applied in the preparation of N-type silver-aluminum paste. The raw materials for preparing the N-type silver-aluminum paste include, by weight: 2.5 parts of aluminum powder material, 6.5 parts of glass powder, 80 parts of silver powder, and 10 parts of organic carrier.

[0044] The glass powder is PbO-B2O3-ZnO-SiO2 series glass powder, has a softening temperature of 300-500°C, and a particle size D50 of 0.6-2 μm.

[0045] The particle size D50 of the silver powder is 1-3 μm.

[0046] The organic carrier comprises, by weight, 1.5 parts of a binder resin, 4 parts of a solvent and 2.5 parts of an auxiliary agent.

[0047] The binder resin is cellulose acetate butyrate.

[0048] The solvent is diethylene glycol butyl ether acetate.

[0049] The auxiliary agent includes 0.4 parts of dispersant, 0.5 parts of silicone oil and 1 part of thixotropic agent in parts by weight.

[0050] The silicone oil is methyl silicone oil.

[0051] The thixotropic agent is polyethylene wax.

[0052] The dispersant is 0.2 parts by weight of polyether phosphate and 0.2 parts by weight of acrylate.

[0053] The method for preparing the N-type silver-aluminum paste comprises the following steps:

[0054] (1) Mix aluminum powder material and glass powder evenly, add organic carrier, stir evenly, then add silver powder, stir evenly;

[0055] (2) Grind with a three-roll mill for 8 hours and filter with a 500-mesh filter to obtain N-type silver-aluminum slurry.

[0056] Example 2

[0057] An N-type silver aluminum paste, the specific steps are the same as those in Example 1, except that the starting oxidation temperature of the aluminum powder used is 635°C.

[0058] Comparative Example 1

[0059] The raw materials for preparing the N-type silver aluminum paste include, by weight: 2.5 parts of conventional aluminum powder material, 6.5 parts of glass powder, 80 parts of silver powder, and 10 parts of organic vehicle. The median diameter D50 of the aluminum powder in this embodiment is 1-3 μm, and D100 is 8-10 μm. The starting oxidation temperature is 630°C.

[0060] The glass powder is PbO-B2O3-ZnO-SiO2 series glass powder, has a softening temperature of 300-500°C, and a particle size D50 of 0.6-2 μm.

[0061] The particle size D50 of the silver powder is 1-3 μm.

[0062] The organic carrier comprises, by weight, 1.5 parts of a binder resin, 4 parts of a solvent and 2.5 parts of an auxiliary agent.

[0063] The binder resin is cellulose acetate butyrate.

[0064] The solvent is diethylene glycol butyl ether acetate.

[0065] The auxiliary agent includes 0.4 parts of dispersant, 0.5 parts of silicone oil and 1 part of thixotropic agent in parts by weight.

[0066] The silicone oil is methyl silicone oil.

[0067] The thixotropic agent is polyethylene wax.

[0068] The dispersant is 0.2 parts by weight of polyether phosphate and 0.2 parts by weight of acrylate.

[0069] The method for preparing the N-type silver-aluminum paste comprises the following steps:

[0070] (1) Mix aluminum powder material and glass powder evenly, add organic carrier, stir evenly, then add silver powder, stir evenly;

[0071] (2) Grind with a three-roll mill for 8 hours and filter with a 500-mesh filter to obtain an N-type silver-aluminum slurry.

[0072] Comparative Example 2

[0073] An N-type silver aluminum paste, the specific steps are similar to those of comparative example 1, the difference is that conventional aluminum powder is used, and the starting oxidation temperature of the aluminum powder in the comparative example is 608°C.

[0074] Comparative Example 3

[0075] An N-type silver aluminum paste, the specific steps are similar to those of comparative example 1, the difference is that conventional aluminum powder is used, and the starting oxidation temperature of the aluminum powder in this comparative example is 619°C.

[0076] Performance Testing

[0077] The N-type silver aluminum paste prepared in Examples 1-2 and Comparative Examples 1-3 was applied to an N-type topcon solar cell silicon-based cell. The surface electron microscope image of the cell obtained in Comparative Example 1 is shown in FIG. Figure 3 The surface electron microscope image of the cell obtained in Example 1 is shown in Figure 4 .

[0078] The contact resistivity was tested with a TLM (contact resistance tester), the minority carrier lifetime of the cell was tested with a WCT-120 (minority carrier lifetime tester), and J was calculated. 01 , the test results are shown in Table 1.

[0079] Table 1

[0080] <![CDATA[Contact resistivity (mΩ*cm 2 )]]> <![CDATA[J 01 (fA / cm 2 )]]> Example 1 1.2 301 Example 2 1.1 303 Comparative Example 1 1.1 438 Comparative Example 2 2.3 492 Comparative Example 3 2.0 487

[0081] From the results of Example 1 and Comparative Example 1, it can be seen that controlling the aluminum powder D100 to D100 < 4.5 μm can reduce metallization recombination. From the results of Examples 1-2 and Comparative Examples 2-3, it can be seen that the initial oxidation temperature of the aluminum powder material > 625°C can further reduce the contact resistivity and reduce metallization recombination.

Claims

1. An application of aluminum powder material for N-type silver aluminum paste, characterized in that: The median diameter D50 of the aluminum powder material is 1-3 μm, and the maximum particle D100 is less than 4.5 μm; The oxygen content of the aluminum powder material is less than 2%, and the oxidation start temperature of the aluminum powder material is greater than 625°C; The preparation method of the aluminum powder material comprises the following steps: (1) Under the protection of nitrogen gas, the aluminum ingot is heated to 700-1000°C in a smelting furnace to melt into aluminum liquid and keep the temperature, and then the obtained aluminum liquid is transported to an atomization chamber with a mixed gas as the ambient gas through an aluminum liquid guide pipe. At the same time, the mixed gas is sprayed through a tightly coupled gas atomization nozzle to atomize the aluminum liquid to form atomized aluminum liquid droplets. Then, under the cooling and protection of the ambient gas, it is cooled and rapidly solidified to form atomized aluminum powder. The cooling temperature is 200-400°C; (2) using a nitrogen-protected airflow pulverizer to classify aluminum powder, and under the protection of nitrogen gas, by adjusting the equipment pressure to 0.5-0.7 MPa and the classifying wheel speed to 270-320 Hz, the aluminum powder prepared in step (1) is classified into aluminum powder materials with a particle size of less than 4.5 μm; The mixed gas is a mixed gas of nitrogen and oxygen, and the volume fraction of oxygen is 1-4%; The aluminum powder material is used in the preparation of N-type silver aluminum paste. The raw materials for preparing the N-type silver aluminum paste include, by weight: 0.5-3 parts of aluminum powder material, 3-10 parts of glass powder, 70-90 parts of silver powder, and 5-15 parts of organic carrier.

2. The use of aluminum powder material for N-type silver aluminum paste according to claim 1, characterized in that: The shape of the aluminum powder material is selected from spherical, flake and star-shaped.

3. The use of aluminum powder material for N-type silver aluminum paste according to claim 1, characterized in that: The glass powder is PbO-B2O3-ZnO-SiO2 series glass powder, has a softening temperature of 300-500°C, and a particle size D50 of 0.6-2 μm.

4. The use of aluminum powder material for N-type silver aluminum paste according to claim 3, characterized in that: The particle size D50 of the silver powder is 1-3 μm.

5. The use of aluminum powder material for N-type silver aluminum paste according to claim 1, characterized in that: The organic carrier is a mixture comprising a binder resin, a solvent and an auxiliary agent, and the binder resin is selected from one or a combination of acrylic resin, ethyl cellulose, cellulose acetate butyrate, PVB and hydrogenated rosin ester resin.

6. The use of aluminum powder material for N-type silver aluminum paste according to claim 5, characterized in that: The solvent is selected from one of diethylene glycol dibutyl ether, diethylene glycol butyl ether acetate, diethylene glycol butyl ether, dimethyl adipate, alcohol ester dodecahydrate, tripropylene glycol monomethyl ether, and alcohol ester hexadecene, or a combination of several of them.

7. The use of aluminum powder material for N-type silver aluminum paste according to claim 1, characterized in that: The method for preparing the N-type silver-aluminum paste comprises the following steps: (1) Mix aluminum powder and glass powder evenly, add organic carrier, stir evenly, then add silver powder and stir evenly; (2) Grind with a three-roll mill for 5-8 hours and filter with a 500-mesh filter to obtain N-type silver-aluminum slurry.

Citation Information

Patent Citations

  • Aluminium powder for aluminium slurry of crystalline silicon solar battery, preparation method thereof, and solar battery containing aluminium powder

    CN104157330A

  • Method for preparing superfine spherical aluminum powder by high-pressure atomization

    CN111633215A

  • N-type high-efficiency battery front silver-aluminum paste

    CN112489851A

  • Silver-aluminum paste for front fine grid of high-performance N-type solar cell and preparation method of silver-aluminum paste

    CN113257457A

  • Electrode slurry that makes contact with p+ emitter of n-type solar cell

    EP4040449A1